Miroslav Volf’s public theology in national healing and reconciliation in Zimbabwe - Joseph C. Useni; Wim A. Dreyer (Verbum et Ecclesia)
Several individuals use Miroslav Volf’s theology to understand the unity of systematic theology and biblical interpretation, as well as the relationship between church theology and political theology. As a result, his work is associated with politically engaged and well-known theologians such as David Tracy, Reinhold Niebuhr and Jurgen Moltmann. It would be more beneficial to interpret Miroslav Volf’s critical work as an attempt to clarify terms such as ‘common good’, ‘embracing’ and ‘justice’. In addition to examining the political and socioeconomic environment and social exclusion in Zimbabwe, this study encourages a ‘historical-theological’ critique of social justice and social injustice.